Exploring the impacts of tourism and weather on water consumption at different spatiotemporal scales: evidence from a coastal area on the Adriatic Sea (northern Italy) - Mazzoni, Filippo; Marsili, Valentina; Alvisi, Stefano; Franchini, Marco (Environmental research, infrastructure and sustainability : ERIS, 2022)
The growth of tourism in the last decades has left behind a significant footprint on water resources, which is particularly evident in the regions affected by water scarcity or consistent seasonal population fluctuations. However, only limited efforts were spent in evaluating the effects of tourism on water consumption with regard to specific non-residential users such as bathing facilities. The current work aimed at providing an insight into the effects of seaside tourism on water consumption in a case study coastal area in northern Italy that is typically subjected to high tourist fluctuations throughout the year. Analyses were carried out at multiple spatiotemporal scales—from urban to user level, and from yearly to daily scale—by exploiting hourly flow data collected at the inflow points of the area and at some touristic users (i.e. nine bathing facilities and a holiday home). In addition, the impact of weather—temperature and rainfall—on water use was explored. The study revealed consistent inflow fluctuations in the area concerned based on tourism (with a ratio between the maximum and minimum monthly average inflow of about 15.7) and demonstrated that the touristic component of water inflow was considerably higher than the residential component at the height of tourist season (i.e., 176 L/s against 42 L/s). Moreover, significant variations in the water inflow due to tourism and weather were also observed on a daily scale, along with considerable water consumption fluctuations in bathing facilities.